The Influence of Apple and Snakefruit Vinegar on Blood Glucose Levels of Male Wistar Rats Fed with High-Sugar Diet - Zubaidah, Elok (Jurnal Teknologi Pertanian, 2011)
Vinegar is a liquid that produced from starch and sugar-contained material by alcoholic and acetic fermentation. Usually, vinegar is made from fruits including apple and snakefruit. Apple and snakefruit vinegar contains natural antioxidants that able to neutralize free radicals from oxidation reactions therefore prevents degenerative deseases. This study was objected to know the effect of apple and snakefruit vinegar to reduce blood glucose levels on male Wistar rats fed a high-sugar diet, and to compare the effectivity of apple vinegar and snakefruit vinegar on blood glucose decline.Â  This study is a laboratory experimental with Post Test Only Control Group Design. Rats were divided into four groups (normal diet, high-sugar diet, high-sugar diet + apple vinegar, and high-sugar diet + snakefruit vinegar.Â  The result showed that apple vinegar and snakefruit vinegar lowered blood glucose levels near to normal. High sugar-diet group (211.0 mg/dl) revealed a significant glucose level difference compared to normal diet (156.3 mg/dL), high sugar-diet + apple vinegar (146.3 mg/dL), and high sugar-diet + snakefruit vinegar group (132.7 mg/dL). Keywords: apple vinegar, snakefruit vinegar, high sugar-diet